Cell migration and growth induced by photo-immobilised vascular endothelial growth factor (VEGF) isoforms. Issue 27 (12th June 2019) - Ren, Xueli; Akimoto, Jun; Miyatake, Hideyuki; Tada, Seiichi; Zhu, Liping; Mao, Hongli; Isoshima, Takashi; Müller, Stefan; Kim, Seong Min; Zhou, Yulai; Ito, Yoshihiro
Abstract : VEGF isoforms immobilised by photo-reactive gelatin (AzPhe-gelatin) enhance cell migration and proliferation. Abstract : Vascular endothelial growth factors (VEGFs) play an important role in tissue repair and regeneration. In this study, VEGFs were immobilised by photo-reactive gelatine by photo-irradiation and the effect of immobilisation was quantitatively investigated. Immobilised VEGFs enhanced endothelial cell migration and growth more than soluble VEGFs. In addition, the activation effects depended on the VEGF isoforms. Prolonged activation of phosphorylation sites in the VEGF receptor, which is associated with migration and proliferation, was observed on the immobilised VEGF surfaces. The results indicated that photo-immobilised VEGFs induced high cell activation by stimulating phosphorylation of the VEGF receptor, VEGFR2, which activated multiple cell functions.